Insulin Receptor Substrate 2 Controls Insulin-Mediated Vasoreactivity and Perivascular Adipose Tissue Function in Muscle - Turaihi, Alexander H.; Bakker, Wineke; van Hinsbergh, Victor W. M.; Serné, Erik H.; Smulders, Yvo M.; Niessen, Hans W. M.; Eringa, Etto C. (Frontiers in Physiology, 2018)
Introduction: Insulin signaling in adipose tissue has been shown to regulate insulin’s effects in muscle. In muscle, perivascular adipose tissue (PVAT) and vascular insulin signaling regulate muscle perfusion. Insulin receptor substrate (IRS) 2 has been shown to control adipose tissue function and glucose metabolism, and here we tested the hypothesis that IRS2 mediates insulin’s actions on the vessel wall as well as the vasoactive properties of PVAT. Methods: We studied PVAT and muscle resistance arteries (RA) from littermate IRS2+/+ and IRS2-/- mice and vasoreactivity by pressure myography, vascular insulin signaling, adipokine expression and release and PVAT morphology. As insulin induced constriction of IRS2+/+ resistance arteries in our mouse model, we also exposed resistance arteriesRA’s of C57/Bl6 mice to PVAT from IRS2+/+ and IRS2-/- littermates to evaluate vasodilator properties of PVAT. Results: IRS2-/- RA exhibited normal vasomotor function, yet a decreased maximal diameter compared to IRS2+/+ RA. IRS2+/+ vessels unexpectedly constricted endothelin-dependently in response to insulin, and this effect was absent in IRS2-/- RA due to reduced ERK1/2activation. For evaluation of PVAT function, we also used C57/Bl6 vessels with a neutral basal effect of insulin. In these experiments insulin [10.0 nM] increased diameter in the presence of IRS2+/+ PVAT (17±4.8, p=0.014), yet induced a 10±7.6% decrease in diameter in the presence of IRS2-/- PVAT. Adipocytes in IRS2-/- PVAT (1314±161µm2) were larger (p=0.0013) than of IRS2+/+ PVAT (915±63µm2). Adiponectin, IL-6, PAI-1 secretion were similar between IRS2+/+ and IRS2-/- PVAT, as were expression of pro-inflammatory genes (TNF-α, CCL2) and adipokines (adiponectin, leptin, endothelin-1). Insulin-induced AKT phosphorylation in RA was similar in the presence of IRS2-/- and IRS2+/+ PVAT. Conclusion:In muscle,IRS2 regulates both insulin’s vasoconstrictor effects, mediating ERK1/2-ET-1 activation, and its vasodilator effects, by mediating the vasodilator effect of PVAT. The regulatory role of IRS2 in PVAT is independent from adiponectin secretion.